SENSOR VISUAL UNTUK PENGUKURAN TINGGI GOA BERBASIS PERANGKAT ANDROID - , AHMAD NURDIANSYAH ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Hilly area in Yogyakarta and Central Java region have caves which have the potency to be developed as tourism and research areas. One of such data needed for these developments is the height of the cave. Programming technology nowadays has developed rapidly, especially after the Android operating system on mobile phones allows the user to enter the program into it. This study was conducted by optimizing sensors available on mobile phones and the Pythagorean theorem to take measurements of the height of the room. Image processing was used in this research to process the laser beam captured by the front camera on mobile phones with the Android operating system. Once the file is received by the sensor on the cell phone camera, the file is processed using the programming system to measure the distance from the tip of the laser pointer until it is reflected by the ceiling. The study was conducted on two places which were indoor room and Seplawan cave, to measure the device accuracy on two objects with different difficulty levels. At first object the accuracy reached more than 99% with a precision of 1.43%. While the accuracy of the second object reached more than 98% and a precision of 1.80%. For the measurement in the cave, the research took a different variation of altitude conditions to determine the accuracy of this device.